Sizing sub-diffraction limit electrosprayed droplets by structured illumination microscopy. Issue 1 (15th November 2017) - Hollerbach, Adam; Logsdon, David; Iyer, Kiran; Li, Anyin; Schaber, J. Andy; Graham Cooks, R.
Abstract : Electrosprayed droplets are widely studied for their role in the formation of ions at atmospheric pressure. Abstract : Electrosprayed droplets are widely studied for their role in the formation of ions at atmospheric pressure. Most droplet measurement methods used today employ light scattering to infer information about an electrosprayed droplet's size. However, these methods fail to measure droplets smaller than about 400 nm in diameter due to constraints imposed by the diffraction limit of light. To overcome this limitation, a super resolution fluorescence microscopy-based method for determining the sizes of electrosprayed droplets has been developed. Solutions containing rhodamine B and different amounts of glycerol were paper sprayed and nanoelectrosprayed onto conductive microscope coverslips using a single, high voltage pulse. Images of the deposited droplets were collected using a super resolution microscope operating in 3D structured illumination microscopy mode (3D-SIM). The sizes of droplets were measured using a modified circular Hough transformation program in Matlab. On average, the diameters of paper sprayed droplets were between 500 nm and 2 μm while almost all nanoelectrosprayed droplets were smaller than 1 μm. The center of a paper spray plume exhibited larger droplets than those at the periphery, likely due to greater Coulombic repulsive forces acting on the smaller droplets to drive them outwards. The periphery also likely contained progeny droplets in addition to smaller parent droplets. It was possible to alter the sizes of nanoelectrosprayed droplets in several ways, including by changing the solvent composition and voltage applied to the emitter. Droplets consisting of high concentrations of glycerol were larger than droplets containing high concentrations of methanol, presumably due to the high surface tension of glycerol. Correspondingly, droplets became smaller when the voltage applied to the emitter was increased, likely due to the ability to overcome the surface tension of the solvent more easily. The smallest detectable droplets confidently measured with this method were 200 nm in diameter. This method demonstrates a new way of measuring the sizes of electrosprayed droplets with half the diameter of conventional droplet size measurement methods. Through further optimization, it may be possible to measure the sizes of electrosprayed droplets as small as the theoretical resolution limit of SIM (∼100 nm).